2012
DOI: 10.1111/j.1468-3083.2012.04455.x
|View full text |Cite
|
Sign up to set email alerts
|

An Internet‐based programme to promote adequate UV exposure behaviour in adolescents in Spain

Abstract: This is the first study to demonstrate that a programme entirely conducted via Internet significantly reduces by half self-reported sunburn risk in an adolescent population achieving very high satisfaction rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
1
19
1
Order By: Relevance
“…2 In this study, 113 adolescents received SMS messages focused on skin cancer prevention. In contrast to previous studies involving adolescents, 6,8,3034 participants reported significant behavioral changes. Novel to this study were reports that some participants received, read, and discussed content with others.…”
Section: Discussioncontrasting
confidence: 99%
“…2 In this study, 113 adolescents received SMS messages focused on skin cancer prevention. In contrast to previous studies involving adolescents, 6,8,3034 participants reported significant behavioral changes. Novel to this study were reports that some participants received, read, and discussed content with others.…”
Section: Discussioncontrasting
confidence: 99%
“…Sun protection behaviour did not change and results on tanning behaviour were mixed. These mixed results are typical of the few sun protection education intervention studies that have been conducted with adolescents [32,[61][62][63][64][65][66]. For example, a study that used self-report to measure sun protection behaviours and intentions pre-and post-the delivery of 36 SMS over 12 weeks found significant changes in some behaviours/intentions e.g., use of sunscreen but not others e.g., seeking shade and intentional tanning [40].…”
Section: Discussionmentioning
confidence: 95%
“…Sun protection behaviour did not change and results on tanning behaviour were mixed. These mixed results are typical of the few sun protection education intervention studies that have been conducted with adolescents [31,[60][61][62][63][64][65]. For example, a study that used self-report to measure sun protection behaviours and intentions preand post-the delivery of 36 SMS over 12 weeks found significant changes in some behaviours/intentions e.g., use of sunscreen but not others e.g., seeking shade and intentional tanning [39].…”
Section: Discussionmentioning
confidence: 98%